2005
DOI: 10.1159/000088094
|View full text |Cite
|
Sign up to set email alerts
|

Use of 3-Dimensional Computed Tomography Reconstruction Studies in the Preoperative Assessment of Patients Undergoing Balloon Dilatation for Tracheobronchial Stenosis

Abstract: Background: Balloon dilatation (BD) is a useful method of treating tracheobronchial stenosis (TBS); however, accurate preoperative identification of the lesion is difficult. Three-dimensional computed tomography (3D-CT) is an imaging method that may allow more accurate definition of the lesion(s) preoperatively. Study Objective: It is the aim of this study to present our finding using 3D-CT as a part of the preoperative evaluation of patients with TBS undergoing BD. Methods: We studied a prospective case serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Third, bronchoscopy cannot reveal the peribronchial or mediastinal lymph node enlargement. Chest CT with 3-dimensional reconstruction may compensate for this disadvantage of bronchoscopy, which allows for a more accurate definition of the airway and will demonstrate the anatomy of the lesion with respect to other mediastinal organs and great vessels [22]. In this study, chest CT detected bronchial narrowing ranging from total obstruction to near-normal stenosis in as much as 87.5% of patients with the exception of 1 case of mild mucosal lesion and 1 case of segmental bronchial lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Third, bronchoscopy cannot reveal the peribronchial or mediastinal lymph node enlargement. Chest CT with 3-dimensional reconstruction may compensate for this disadvantage of bronchoscopy, which allows for a more accurate definition of the airway and will demonstrate the anatomy of the lesion with respect to other mediastinal organs and great vessels [22]. In this study, chest CT detected bronchial narrowing ranging from total obstruction to near-normal stenosis in as much as 87.5% of patients with the exception of 1 case of mild mucosal lesion and 1 case of segmental bronchial lesion.…”
Section: Discussionmentioning
confidence: 99%
“…On group of authors found that, in patients with tracheobronchial stenosis, reconstruction CT has a sensitivity of 100%. (9) It is essential to rule out the presence of any type of concomitant laryngeal lesion prior to repairing the tracheal lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The required length of balloon is estimated by passing the bronchoscope through the stenosis and by measuring the distance between the proximal and distal limits of the obstruction. Three-dimensional CT is a useful noninvasive evaluation for BBD (Rooney et al, 2005). It allows for preoperative determination of balloon size and length, even if the bronchoscope cannot be passed through the obstruction.…”
Section: Wwwintechopencommentioning
confidence: 99%